2000
DOI: 10.1076/0928-6586(200003)711-2ft013
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and risk factors for cataract among diabetes clinic attenders

Abstract: The incidence of and risk factors for cataract during a mean (standard deviation (SD)) follow-up period of 5.0 (3.0) (range 0.1-12.4) years were examined among 3606 patients (2001 male and 1605 female) with diabetes mellitus from three outpatient clinics at the University Hospital, Nottingham. Among the 3606 patients free of cataract at initial registration who attended the clinic at least twice in the period 1979-1992, the mean (SD) age was 49.2 (17.8) years with a mean (SD) duration of diabetes of 7.6 (9.8) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
3
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 18 publications
4
34
3
1
Order By: Relevance
“…Age is an accepted risk factor for cataract, and 12 studies accounted or controlled for age or for age and sex in their analyses. Nine studies found an association between smoking and cataract, 11,[20][21][22][23]31,34,35,40 and only 3 studies 25,36,38 found no association after adjustment for age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Age is an accepted risk factor for cataract, and 12 studies accounted or controlled for age or for age and sex in their analyses. Nine studies found an association between smoking and cataract, 11,[20][21][22][23]31,34,35,40 and only 3 studies 25,36,38 found no association after adjustment for age.…”
Section: Discussionmentioning
confidence: 99%
“…Although most studies distinguished between nuclear, cortical, and posterior subcapsular cataract, some studies did not and grouped all types together for analysis. 5,9,22,25,26,37,38,49 Standardized criteria for diagnosis of cataract were used in some studies. The Lens Opacities Classification System 50,51 or later updated versions of this system was used in 5 studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En la tabla 1 se presentan los diferentes submodelos que se incluyen en el análisis, así como los dife-rentes estados de salud que contemplan cada uno de ellos. Las probabilidades de transición están basadas en diferentes estudios clí-nicos [13][14][15][16][17] y varían con el tiempo y con el perfil de riesgo de la población de estudio.…”
Section: El Modelo De Coreunclassified
“…Cross-sectional findings from the Beaver Dam Eye Study 744 and the POLA Study 745 , indicated associations between diabetes and both cortical and PSC cataract, while the Barbados Eye Study 746 reported an association only with cortical cataract. Many studies, including case reports and population surveys, have also found associations between diabetes and all lens opacities 733 , very early or rapid-onset cortical opacities [747][748][749] , and cataract surgery [750][751][752] .…”
Section: Cataract In Diabetesmentioning
confidence: 99%